(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2019)
Physical and geographical characteristics of the Orzhytsia River valley with Hnyla Ornitsa tributary are presented. Variety of habitats included in the list of the Resolution 4 of the Bern Convention enables considering this territory as a promising object of the Ukraine Emerald Network. This is facilitated by availability of a number of objects of the Nature Reserve Fund of Ukraine («Orzhitskyi» and «Timkivskyi» hydrological reserves, «Plysiv Yar» botanical reserve, «Zagat» protected ecosite etc.) in the studied territory. 17 Emerald habitats have been established for the Orzhytisa River valley, their ecological and coenotical characteristics and features of territorial distribution are given. General evaluation of botanical component of the vegetation types has been carried out, as well as location of rare plant species on this territory, included in the Sozological Lists of different ranks (regional (9 species), national (the Red Book of Ukraine – 5) and international (in particular, Bern Convention – 3). It is necessary to preserve and protect the rare species populations of Iris hungarica, Jurinea cyanoides, Ostericum palustre, which, having other sozological statuses, are included in the Annex I of the Resolution 6 of the Bern Convention (1998). Some measures of ecological management of this territory are suggested, in particular it is expedient to prohibit further plowing of the terrain, drainage of floodplain areas, afforestation of meadow-steppe slopes, burning of dry grass and stimulation of grass mowing of grasses and their grazing by running type.